The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1476-5381.1990.tb14715.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of non‐specific airway hyperreactivity after allergen challenge in guinea‐pigs by the PAF receptor antagonist SDZ 64–412

Abstract: Allergen challenge by aerosol in sensitized guinea‐pigs elicited non‐specific airway hyperreactivity assessed by reactivity to i.v. histamine or acetylcholine. Airway hyperreactivity to histamine persisted for at least 48 h and was accompanied by pulmonary eosinophilia as determined by bronchoalveolar lavage cell analysis. Airway hyperreactivity was independent of vagal reflex mechanisms since it was not abrogated by bilateral vagotomy. The novel platelet‐activating factor (PAF) receptor antagonist SDZ 64–412 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…Non-specific airway hyperreactivity to i.v. histamine or acetylcholine which was elicited by aerosol allergen challenge in sensitized guinea-pigs 24h after challenge, persisted for at least 48h and was inhibited by PAF-antagonist, ketotifen or methylprednisolone (Havill et al, 1990). In the present experiments, we found that the hyperreactivity was induced within 6min after the administration of ovalbumin, at a dose which was insufficient to induce an increase in ITP.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Non-specific airway hyperreactivity to i.v. histamine or acetylcholine which was elicited by aerosol allergen challenge in sensitized guinea-pigs 24h after challenge, persisted for at least 48h and was inhibited by PAF-antagonist, ketotifen or methylprednisolone (Havill et al, 1990). In the present experiments, we found that the hyperreactivity was induced within 6min after the administration of ovalbumin, at a dose which was insufficient to induce an increase in ITP.…”
Section: Discussionmentioning
confidence: 51%
“…Although the exact mechanism of hyperreactivity has not yet been elucidated, PAF-induced inflammatory events, such as leucocyte invasion of the thorax, oedema formation and impaired mucus clearance are thought to have important roles (Lellouch-Tubiana et al, 1988). Despite a lack of correlation between airway hyperreactivity and the presence of eosinophils in bronchial alveolar fluids (Havill et al, 1990), the role of eosinophils has generally been a topic of much attention (Durham & Kay, 1985;Sanjar et al, 1989). Cockcroft et al (1983) and Sanjar et al (1989) found that the accumulation of sufficient eosinophils in the airway lumen requires more than 1 h or days.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data indicate that PAF may be involved in antigen-induced airway hyperresponsiveness. In contrast, the lack of effect of these agents on eosinophil recruitment suggest that the presence of eosinophils alone is not a prerequisite to the development of allergen-induced airway hyperresponsiveness (Havill et al, 1990;Ishida et al, 1990).…”
Section: Eosinophils and Antigen-induced Airway Hyperresponsivenessmentioning
confidence: 99%
“…The possibility of rapid metabolism of acetylcholine did not prevent the demonstration of airway hyperresponsiveness to this spasmogen in both IgG-and IgE-based models (Coyle et al 1988;Havill et al 1990;Noonan et al 1991;Arimura et al 1994). Methacholine was used as the muscarinic agonist, in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…1988Daffonchio et ul. & 1989Nieri et al 1992;Underwood et al 1992) or that which may follow the late asthmatic response (Coyle et al 1988;Havill et al 1990;Sanjar et a1. 1990;Noonan et al 1991;Farmer et al 1992;Handley et ul.…”
mentioning
confidence: 99%